PENGARUH KUALITAS LAYANAN DAN NILAI NASABAH TERHADAP LOYALITAS NASABAH BANK BRI KK UNISMA MALANG - Richi Irawan; N Rachma (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThe purposeof this study to determine the effect of Service Quality and Customer Value simultaneously and partially on customer loyality bank Bri Kk Unisma malang.the sampling technique using accidental. Data analysis tool used in this research is multiple linear regression analysis.Based on the results of this study note that the count value of 8,737 with a value of 0,000<0,05 so that is can be concluded that Service Quality and Customer Value effect simultaneously to customer loyality. And partially effect on Customer Loyality. And there is one variable that is Customer Value variable which has no partial effect.Keywords : Service Quality, Customer Value and Customer loyality